Violence in Peru: how to promote a culture of peace? - Huamán Chura, Katthia (2019)
Peru is going through difficult times; the media give us scope of the painful social situation in which we live. This is where the trite phrase, which describes the human as “The only predator capable of harming his own species”, might apply. The damage caused by this predator can be verbal, psychological, physical and sexual; it can even take the life of others. The ghost of violence is everywhere, in homes, study centers, neighborhoods and in the whole country. The figure is alarming, each year, according to the World Health Organization, 1.4 million people die as a result of violence (WHO, 2014b), not to mention the extent of victims who are affected in other ways,in the short, medium and long term. The present article reviews the most relevant edges of thissocial phenomenon and presents a brief collection of proposals to face it from a Culture of Peaceapproach.